Introducing Angle B: A Novel Quantitative Approach for Sagittal Alignment Reduction in Atlanto-Axial Dislocation Surgery - Cui S; Wang X; Li K; Feng H; Liu Z; Jian F; Wang K (Dove Medical Press, 2024)
Shengyu Cui,1- 4 Xinyu Wang,1- 5 Kang Li,1- 4 Hailong Feng,6 Zhenlei Liu,1- 4 Fengzeng Jian,1- 4 Kai Wang1- 4 1Department of Neurosurgery, Xuanwu Hospital, Capital Medical University, Beijing, People's Republic of China; 2Spine Center, China International Neuroscience Institute (CHINA-INI), Beijing, People's Republic of China; 3Research Center of Spine and Spinal Cord, Beijing Institute of Brain Disorders, Capital Medical University, Beijing, People's Republic of China; 4Lab of Spinal Cord Injury and Functional Reconstruction, China International Neuroscience Institute (CHINA-INI), Xuanwu Hospital, Capital Medical University, Beijing, People's Republic of China; 5Baylor College of Medicine, Huston, TX, USA; 6Department of Neurosurgery, Sichuan Academy of Medical Sciences and Sichuan Provincial People's Hospital, Chengdu, People's Republic of ChinaCorrespondence: Fengzeng Jian; Kai Wang, China International Neuroscience Institute (CHINA-INI), Xuanwu Hospital, Capital Medical University, No. 45 Changchun Street, Xicheng District, Beijing, 100053, People's Republic of China, Tel +86-1083198277, Email jianfengzeng@xwh.ccmu.edu.cn; sammas1883@sina.comObjective: This study aims to establish a quantitative relationship between cervical lordosis (CL) and the rotation angle of the axis for the surgical reduction of atlantoaxial dislocation (AAD) and to explore the potential applications of this relationship in preoperative planning and selection of surgical techniques.Methods: To construct the correlation between horizontal gaze and location of axis, we introduced the angle B, defined as the angle between the Frankfort horizontal line and the extension line of the posterior edge of the axis, and explored its application in surgical planning. We retrospectively analyzed imaging data from computed tomography of 23 AAD patients who had undergone posterior reduction and fixation. Theoretical equations were deduced through a series of angular transformations, and linear regression analysis was used to validate our findings.Results: Our results showed a strong linear relationship between the change in CL (ΔCL) and the change in B(ΔB) (y=− 1.0402x, coefficient of determination R²=0.978, P< 0.001), supporting our deduction that ΔCL=ΔB. Furthermore, we found that the rotation angle of the axis (angle D) was equal to ΔCL. By resolving the atlantoaxial interval into the vertical dimension (h) and horizontal dimension (d), we could calculate the maximum vertical and horizontal distance that the axis could move theoretically according to a patient's maximum ΔCL. This finding supports our theory that the introduction of angle B can provide more precise preoperative planning and surgical technique selection for patients with AAD.Conclusion: By introducing angle B and deducing the equation ΔB=ΔCL=D, we have provided an innovative tool for preoperative planning and surgical technique selection for patients with AAD. This equation not only helps surgeons achieve more precise and effective surgical reductions but also emphasizes the important role of angle B in surgical planning.Keywords: quantitative method, sagittal alignment reduction, atlanto-axial dislocation surgery